The impact of exercises using certain educational tools on students learning some basic football skills - Mohammed, Prof. Dr. Yassin Omar; Ali, Honar Anwar (Sulaimani Journal for Humanities, 2025)
This study aimed to develop and implement specific exercises using educational tools with college students to teach them some basic football skills. It also sought to identify the impact of these exercises on students' learning of certain fundamental football skills (passing, dribbling, and shooting), and to determine which exercises were more effective than those used in teaching these specific skills. The study also aimed to determine the effectiveness of these exercises compared to existing training methods in teaching these fundamental football skills. The researchers used the experimental method by designing two groups, one experimental and one control, with pre- and post-tests. The population was defined as the third-year students in the Department of Physical Education at the College of Physical Education and Sports Sciences - University of Sulaimani for the academic year 2024-2025, with a total of (84) students distributed across four sections. To form the two research groups, the researcher chose sections (B, C) as the research sample in a systematic random manner, which amounted to (18, 22) respectively for the two sections. At the end of the research, the sample was limited to (37) students for the two groups, after excluding (3) students from the experimental group due to their absence in the post-test. The research variables (physical and skill-based) were then identified, along with appropriate tests to measure them. Two pilot tests and exercises were conducted to establish the scientific basis for the tests, ensure homogeneity and equivalence between the two groups, and prepare specialized exercises using assistive teaching aids. The research procedures included a pre-test, application of the specialized exercises, and a post-test. The collected data were processed using the SPSS statistical package.
Keywords: Special exercises; teaching aids; learning; basic skills